Heteropoly acid/NaY zeolite as a reusable solid catalyst for highly efficient synthesis of gem-dihydroperoxides and 1, 2, 4, 5-tetraoxanes. (December 2016) - Khosravi, Kaveh; Zendehdel, Mojgan; Naserifar, Shirin; Tavakoli, Fatemeh; Khalaji, Kobra; Asgari, Atefeh
Gem-Dihydroperoxides and 1, 2, 4, 5-tetraoxanes were synthesised from aldehydes and ketones catalysed by heteropoly acid/NaY zeolite (HPA/NaY) as a new, effective and reusable solid catalyst using 30% aqueous hydrogen peroxide at room temperature. The reactions proceeded with high rates and excellent yields.